UNSUR ETNOMATEMATIKA YANG TERKANDUNG PADA BAHASA SUKU TUBBE SEBAGAI SUMBER BELAJAR BILANGAN SISWA SEKOLAH DASAR - Koly, Lay Sintia; Manapa, Imanuel Yosafat Hadi; Saetban, Antonius Abednego (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The purpose of this research is to explore ethnomathematical elements contained in the language of the Tubbe tribe which is then associated with the context of learning student numbers in elementary schools. The research method used in this study is qualitative research method with exploratory, descriptive, and ethnographic approaches. The results of this study are in the form of classification of place values and number construction based on the language structure of the Tubbe tribe. In addition, the results of this study are in the form of a set of numbers contained in the Tubbe Tribe language, namely the set of natural, digit, prime, composite, integers, rational, decimal, irrational, and rill numbers. Some mathematical concepts in numbers such as root and negative forms are not found in the Tubbe language. Thus, to relate the language of the Tubbe tribe to the context of number learning in elementary schools must still be linked to mathematical concepts using Indonesian language.